A review of the Oriental planthopper genus Sogana Matsumura 1914 (Hemiptera: Fulgoromorpha: Tropiduchidae) with descriptions of three new species - Liang, Ai-Ping; Wang, Rong-Rong (Zootaxa, 2008)
The Oriental planthopper genus Sogana Matsumura, 1914 (Hemiptera: Fulgoromorpha: Tropiduchidae) is reviewed and seven species including three new species are recognized in the genus: S. clara sp. nov. (Laos: Vientiane), S. extrema Melichar, 1914 (Burma, China), S. hopponis Matsumura, 1914 (type species, China, Japan), S. longiceps Fennah, 1978 (China, Vietnam), S. pseudohopponis sp. nov. (Laos: Nam Kading), S. robustocarina sp. nov. (Malaysia: Borneo) and S. stimulata Melichar, 1914 (Indonesia: Mentawei Islands). The genus and its included species are described and illustrated. A key to the known species in the genus is provided.